Research on data loss probability and its impact of CTCS-3 train ground communication based on GSM-R - Xia ZHANG; Lian-chuan MA; Yuan CAO; Yu-zhuo ZHANG (Tongxin xuebao)
In order to solve the problem that Euroradio's safe functional module (SFM) of CTCS-3 train control system can not apply protective measures for time-related transmission risks,communication model and failure recovery model for transmission of CTCS-3 train control system are built which based on deterministic and stochastic Petri nets (DSPN).Combining the two models and using TimeNET 4.0 to simulate the result of data loss probability,a conclusion can be concluded that even considering that only data loss will cause dangerous of train control system,the result still can not meet the requirement of SIL4 based on the relevant specification for the CTCS-3.